Implementation of Prophetic Education in Naming the Character of Student at Madrasah Aliyah Islamiyah Malo - Chala, Ni'mal; Kojin, Kojin; Tanzeh, Ahmad; Fuadi, Imam (PT. Riset Press International, 2025)
The purpose of this study is to find out how prophetic education affects character education in Madrasah Aliyah Islamiyah Malo. Qualitative methods are used to gain a deeper understanding of how prophetic values are integrated in the learning process and shape the character of students. Madrasah heads, madrasah deputy heads for public relations, curriculum fields, and teachers were also interviewed to obtain data. The results of the study show that prophetic education is applied through various activities that take place daily and weekly. However, in its implementation, there are several obstacles, such as the limitation of worship infrastructure that is not spacious and the influence of the environment outside the madrasah that is difficult for teachers to control. This causes the application of prophetic education to not be fully optimal. Therefore, synergy is needed between madrassas and parents in guiding and overseeing the behavior of students so that character formation in accordance with prophetic values can run more effectively.